Interactive Effect of Export Strategic Orientations on Export Market Learning Ambidexterity: A Study of Turkish Export SMEs - Unal, Nesibe Nur (International Journal of Applied Research in Management and Economics, 2022)
The interactive effect of export strategic orientations on export market learning ambidexterity has been studied in this paper. Export market orientation and export entrepreneurial orientation, as strategic orientations, have a complement feature among them, while ambidexterity itself is a complement form of exploration and exploitation. In this study, the relationship between these two complement effects was examined by using 291 export SMEs located in Turkey which is an emerging economy. According to the results, a great impact from interactive effect of strategic orientations to ambidexterity is examined. Also, in line with the previous researches, the results confirmed that export strategic orientations individually have impact on exploration and exploitation. The findings help provide a more complete understanding of how export strategic orientations might be related to export market learning dimensions. It is revealed that both types of orientations provide different managerial efforts individually and interactively to develop and foster exploration, exploitation and ambidexterity in export markets.